Procreation and personhood among Ticuna indigenous peoples in the Peruvian Amazon - Chirif, Selva Sofia (2020)
During the last decade there has been an upsurge in the development of mother-child programs based on biomedic conceptions. Drawing on ethnographic material from research with Ticuna indigenous people, I call for the need for dialogue between these programs and indigenous notions of personhood recognizing their influence on the understanding of conception and childcare practices. In this chapter, I explore how Ticuna people conceive the way in which the person is shaped and its influence on each stage of the reproductive cycle, describing the role that different human and non human agents play in this process. Ethnographic research combined participant observation, informal conversations and semi structured interviews with women and man of different ages. This information was analysed with the procreative chronographie technique proposed by Lázare and Fons (2016), which helps to identify the different stages of the procreation cycle from an exegetic point of view.